(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
Through a methodology of an immanent reconstruction of the best argument of those who oppose the legal recognition of same-sex marriage, this article shows why the judge, or the legislator should not accept this argument. With this, it is pointed out indirectly and in a negative way why that marriage should be recognized. In this article the structure and the different contents of the conservative justifications are reconstructed, trying to identify the most robust of them; that is, the one with the highest capacity for –using adequate arguments to plural societies– to transfer the burden of proof to the side of the demand for such recognition. This capacity is demonstrated by showing precisely how such a justification achieves arguments of auto-defense, of criticism of said demand, as well as incorporating arguments from the progressive world. Despite its robustness and after a careful evaluation, it is concluded that this justification is nor sustainable under rational means.